EKSISTENSI TRADISI ANTAR AJONG PADA MASYARAKAT DI DESA KALIMANTAN KECAMATAN PALOH KABUPATEN SAMBAS - Lestari, Juli Wahyu; Rustiyarso, Rustiyarso; Supriadi, Supriadi (Universitas Tanjungpura, 2024)
This study examined the existence of Antar Ajong tradition in Kalimantan Village of Paloh Subdistrict, Sambas Regency. This study used qualitative method which phenomenological approach. Sources of data in this study are traditional leaders and community leaders. Data collection techniques in this study are observation, interviews and documentation. Data analysis in this study uses data analysis according to Miles and Huberman by digging data continuously until the data is saturated. The technique of checking the validity of the data uses observation and triangulation, namely source triangulation, namely comparing and checking information through different sources. The results showed that (1) the existence of the Antar Ajong tradition in the village of Kalimantan showed that the stages of implementing the Antar Ajong tradition were still the same as the ancestral tradition but the implementation process underwent a slight change. (2) the values in the Antar Ajong tradition in the Kalimantan village contain religious, mutual cooperation, tolerance, responsibility and social care. (3) community participation in the Antar Ajong tradition in Kalimantan village in the form of physical and material involvement.